Quantification of methane in humid air and exhaled breath using selected ion flow tube mass spectrometry - Dryahina, Kseniya; Smith, D; Spanel, P (Rapid communications in mass spectrometry, 2010)
In selected ion flow tube mass spectrometry, SIFT-MS, analyses of humid air and breath, it is essential to consider and account for the influence of water vapour in the media, which can be profound for the analysis of some compounds, including H(2)CO, H(2)S and notably CO(2). To date, the analysis of methane has not been considered, since it is known to be unreactive with H(3)O(+) and NO(+), the most important precursor ions for SIFT-MS analyses, and it reacts only slowly with the other available precursor ion, O(2) (+). However, we have now experimentally investigated methane analysis and report that it can be quantified in both air and exhaled breath by exploiting the slow O(2) (+)/CH(4) reaction that produces CH(3)O(2) (+) ions. We show that the ion chemistry is significantly influenced by the presence of water vapour in the sample, which must be quantified if accurate analyses are to be performed. Thus, we have carried out a study of the loss rate of the CH(3)O(2) (+) analytical ion as a function of sample humidity and deduced an appropriate kinetics library entry that provides an accurate analysis of methane in air and breath by SIFT-MS. However, the associated limit of detection is rather high, at 0.2 parts-per-million, ppm. We then measured the methane levels, together with acetone levels, in the exhaled breath of 75 volunteers, all within a period of 3 h, which shows the remarkable sample throughput rate possible with SIFT-MS. The mean methane level in ambient air is seen to be 2 ppm with little spread and that in exhaled breath is 6 ppm, ranging from near-ambient levels to 30 ppm, with no significant variation with age and gender. Methane can now be included in the wide ranging analyses of exhaled breath that are currently being carried out using SIFT-MS.
Keywords: vzduch; senioři; Humidity; Methane; Analysis of Variance; mladiství; lineární modely; Middle Aged; Sensitivity and Specificity; mužské pohlaví; Mass Spectrometry; Adult; analýza rozptylu; methan; aceton; Linear Models; ženské pohlaví; pára; vlhkost; Humans; dechové testy; Breath Tests; Acetone; Steam; lidé středního věku; senzitivita a specificita; dospělí; Air; Female; Aged; Adolescent; hmotnostní spektrometrie; lidé; Male